Multi-year patterns in testosterone, cortisol and corticosterone in baleen from adult males of three whale species. Issue 1 (21st September 2018) - Hunt, Kathleen E; Lysiak, Nadine S J; Matthews, Cory J D; Lowe, Carley; Fernández Ajó, Alejandro; Dillon, Danielle; Willing, Cornelia; Heide-Jørgensen, Mads Peter; Ferguson, Steven H; Moore, Michael J; Buck, C Loren
Abstract : Baleen from three adult male whales (North Atlantic right, bowhead and blue) contains regularly spaced areas of high testosterone content suggestive of annual testosterone cycles. Patterns in glucocorticoids (cortisol and corticosterone) show potential relationships with breeding-related stress as well as with entanglement in fishing gear and possible disease episodes. Abstract: Male baleen whales have long been suspected to have annual cycles in testosterone, but due to difficulty in collecting endocrine samples, little direct evidence exists to confirm this hypothesis. Potential influences of stress or adrenal stress hormones (cortisol, corticosterone) on male reproduction have also been difficult to study. Baleen has recently been shown to accumulate steroid hormones during growth, such that a single baleen plate contains a continuous, multi-year retrospective record of the whale's endocrine history. As a preliminary investigation into potential testosterone cyclicity in male whales and influences of stress, we determined patterns in immunoreactive testosterone, two glucocorticoids (cortisol and corticosterone), and stable-isotope (SI) ratios, across the full length of baleen plates from a bowhead whale ( Balaena mysticetus ), a North Atlantic right whale ( Eubalaena glacialis ) and a blue whale ( Balaenoptera musculus ), all adult males. Baleen was subsampled at 2 cm (bowhead, right) or 1 cm (blue) intervals and hormones were extracted from baleen powder with methanol, followed by quantification of all three hormones using enzyme immunoassays validated for baleen extract of these species. Baleen of all three males contained regularly spaced peaks in testosterone content, with number and spacing of testosterone peaks corresponding well to SI data and to species-specific estimates of annual baleen growth rate. Cortisol and corticosterone exhibited some peaks that co-occurred with testosterone peaks, while other glucocorticoid peaks occurred independent of testosterone peaks. The right whale had unusually high glucocorticoids during a period with a known entanglement in fishing gear and a possible disease episode; in the subsequent year, testosterone was unusually low. Further study of baleen testosterone patterns in male whales could help clarify conservation- and management-related questions such as age of sexual maturity, location and season of breeding, and the potential effect of anthropogenic and natural stressors on male testosterone cycles.